2016
DOI: 10.1111/bjh.14235
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycarbamide treatment and brain MRI/MRA findings in children with sickle cell anaemia

Abstract: Silent cerebral infarction (SCI) is the most common neurological abnormality among children with sickle cell anaemia (SCA). The effect of hydroxycarbamide (also termed hydroxyurea) on the development and progression of SCI is unclear. We evaluated brain magnetic resonance imaging/angiography (MRI/MRA) in children with SCA receiving long-term hydroxycarbamide therapy. Fifty participants (median 9·4 years, range 1·1-17·3) enrolled in the Hydroxyurea Study of Long-Term Effects (HUSTLE; NCT00305175) underwent brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 45 publications
2
33
1
Order By: Relevance
“…The HUSTLE cohort of patients in the setting of a hydroxycarbamide cohort (Nottage et al , ) and our current study in the setting of an institutional MRI screening programme and standard of care hydroxycarbamide therapy suggest a similar benefit of hydroxycarbamide for overt stroke protection in patients with SCI. Our cohort also suggests that patients with SCI and a normal MRA may prefer hydroxycarbamide to transfusion for secondary CNS protection.…”
Section: Comparison Of New Cns Events In This Study the Hustle Studysupporting
confidence: 61%
See 2 more Smart Citations
“…The HUSTLE cohort of patients in the setting of a hydroxycarbamide cohort (Nottage et al , ) and our current study in the setting of an institutional MRI screening programme and standard of care hydroxycarbamide therapy suggest a similar benefit of hydroxycarbamide for overt stroke protection in patients with SCI. Our cohort also suggests that patients with SCI and a normal MRA may prefer hydroxycarbamide to transfusion for secondary CNS protection.…”
Section: Comparison Of New Cns Events In This Study the Hustle Studysupporting
confidence: 61%
“…Nottage et al () reported 3‐year magnetic resonance imaging (MRI) outcomes in patients who participated in a cohort study of long‐term hydroxycarbamide therapy (HUSTLE), providing early data on the potential impact of hydroxycarbamide in preventing SCI progression. Nineteen (38%) of 50 participants were identified with a SCI on HUSTLE baseline evaluation.…”
Section: Comparison Of New Cns Events In This Study the Hustle Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses from the HUSTLE study reported that children receiving hydroxyurea escalated to MTD may have higher levels of HbF, Hb and MCV compared to children treated with lower doses of hydroxyurea 30 , and that children enrolled on HUSTLE have a low rate of new or worsening cerebrovascular disease 31 , and improved splenic 32 and renal 33,34 function. The current analysis of the HUSTLE study provides new critical clinical information regarding the optimal HbF% target during hydroxyurea therapy in children with SCA.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients who scored as at risk had ever used hydroxyurea as compared with 75% of those who scored as average. Low hemoglobin has been repeatedly identified as independently associated with neurocognition in sickle cell anemia across numerous studies, 6,17,18 with fetal hemoglobin being shown to be protective. 19 Not surprisingly, the SIT trial showed that the use of prophylactic simple transfusions was protective against the development of further silent infarcts with a 58% relative risk reduction.…”
Section: Discussionmentioning
confidence: 99%